Comparison of short-term outcome and serum magnesium levels in premature infants of mothers after magnesium sulfate therapy - Aditiawarman, - (Foundation for Enviromental Protection and Research, 2020)
Background: Magnesium sulfate (MgSO4) is proven to be a neuroprotectant which functions to reduce the risk of cerebral palsy in premature infants, but the effects on the short-term outcome of newborns are still contradictory. This study aimed to analyze differences in short-term outcomes and serum magnesium levels in newborns after given MgSO4 therapy. Methods: This was a prospective cohort study. Subjects were divided into two groups involved preterm infants from mothers who received MgSO4 and pregnant women who did not received MgSO4 as a control. Results: Among sixty subjects, there were significant differences in outcomes for gestational age infants and respiratory distress syndrome (RDS) between two groups (p = 0.011 and p = 0.013, respectively). Whereas, the significance results were found in birth weight (p = 0.306), Apgar scores 1 (p = 0.816) and 5 minutes (p = 0.924), the use of ventilators (p = 0.335), sepsis (p = 0.276), mortality (p = 0.754), and umbilical artery pH (p = 0.123). The magnesium serum levels of mothers who received MgSO4 and control were 3.45±1.65 mg/dl and 1.78±0.23 mg/dl, respectively (p = 0.001), and infants who received MgSO4 and control were 3.10±1.35 mg/dl and 1.74±0.19 mg/dl, respectively (p = 0.001). Conclusion: There were significant differences in infant outcomes only at gestational age and RDS. The magnesium serum levels of newborns in therapy group were higher than control.